Career Development and Job Satisfaction of Teachers of SMA Negeri 1 Darul Imarah Aceh Besar - Jalaluddin, Jalaluddin; Marwan, Marwan; Firmansyah, Juli (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine the career development and job satisfaction of teachers of SMA Negeri 1 Darul Imarah Aceh Besar. The method used in this study is This research uses the expost facto method. This research was conducted at SMA Negeri 1 Darul Imarah Aceh Besar. This research will be conducted from January 2023 to August 2023.Â The population of this study was all teachers at SMA Negeri 1 Darul Imarah Aceh Besar which amounted to 59 people, while the sample in this study amounted to 59 people. The data collection technique used in this study was a survey to SMA Negeri 1 Darul Imarah Aceh Besar by distributing questionnaires to teachers who were used as research samples. The data analysis technique used in this study is descriptive analysis. The results showed that improving the career development system would have an impact on increasing teacher job satisfaction at SMA Negeri 1 Darul Imarah Aceh Besar.